Unveiling the Subtle Threats: The Neurobehavioral Impact of Chlorpyrifos on Girardia tigrina - Saraiva, Althiéris S. (2024)
Chlorpyrifos, an organophosphate insecticide widely used to control agricultural pests, poses a significant environmental threat due to its toxicity and persistence in soil and water. Our work aimed to evaluate the acute (survival) and chronic (regeneration, locomotion, and reproduction) toxicity of chlorpyrifos to the non-target freshwater planarian Girardia tigrina. The 48 h lethal concentration (LC50) of the commercial formulation, containing 480 g L−1 of chlorpyrifos, the active ingredient, was determined to be 622.8 µg a.i. L−1 for planarians. Sublethal effects were translated into a significant reduction in locomotion and delayed head regeneration (lowest observed effect concentration—LOEC = 3.88 µg a.i. L−1). Additionally, chlorpyrifos exposure did not affect planarian fecundity or fertility. Overall, this study demonstrates the potential of chlorpyrifos-based insecticides to harm natural populations of freshwater planarians at environmentally relevant concentrations. The observed toxicity emphasizes the need for stricter regulations and careful management of chlorpyrifos usage to mitigate its deleterious effects on aquatic ecosystems. By understanding the specific impacts on non-target organisms like G. tigrina, we can make more informed suggestions regarding the usage and regulation of organophosphate insecticides, ultimately promoting sustainable agricultural practices and environmental conservation.